Pain Management Considerations in Patients With Opioid Use Disorder Requiring Critical Care. (5th January 2022) - Smith, Kathryn; Wang, Michelle; Abdukalikov, Ruslan; McAullife, Amy; Whitesell, Dena; Richard, Janelle; Sauer, William; Quaye, Aurora
Abstract: The opioid epidemic has resulted in increased opioid‐related critical care admissions, presenting challenges in acute pain management. Limited guidance exists in the management of critically ill patients with opioid use disorder (OUD). This narrative review provides the intensive care unit clinician with guidance and treatment options, including nonopioid analgesia, for patients receiving medications for OUD and for patients actively misusing opioids. Verification and continuation of the patient's outpatient medications for OUD regimen, specifically buprenorphine and methadone formulations; assessment of pain and opioid withdrawal; and treatment of acute pain with nonopioid analgesia, nonpharmacologic strategies, and short‐acting opioids as needed, are all essential to adequate management of acute pain in patients with OUD. A multidisciplinary approach to treatment and discharge planning in patients with OUD may be beneficial to engage patients with OUD early in their hospital stay to prevent withdrawal, stabilize their OUD, and reduce the risk of unplanned discharge and other associated morbidity.